Dikotomisesta transsukupuolisuudesta queeriin transgenderiin? 18–29. - Tainio, Luca (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2015)
The medical discourse has historically been, and still is, the most notable voice in commenting and defining transsexuality and transgendered identities. The medical perspective is based on normative and dichotomous views on gender, which affects the policies related to gender reassignment processes. Producing recognizable normative bodies and unambiguous identities can be seen as the aim of the process. The recent Finnish discussion on the possible creation of a so-called transgender diagnosis indicates, I argue, a change in the views towards a more fluid and queer understanding of gender. By analyzing four medical articles and two speeches delivered by psychiatrist Aino Mattila, I will trace the possible paradigm shift visible in the discussion on transgender. It remains to be seen whether the transgender diagnosis is to form yet another exclusive category, or whether it opens up the whole trans-diagnostics to include more varied experiences and identities.